Initiating the Implementation of Meaningful Public Participation in Forming Regulations in Urban Areas: From the Perspective of Smart Urban Governance - Bani Pamungkas; Edy Sutrisno; Maulana Yusuf (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Participation of community or city citizens is an essential and critical component in achieving a city's sustainable development. Forms of participation are becoming more accessible and widespread, taking advantage of advances in technology, information, and communication. It becomes a policy choice for various global cities and cities in Indonesia to bring about more meaningful or substantial participation and collaboration through elements of smart governance in the realm of the concept of smart cities. As a response to Constitutional Court Decision No. 91/PUU-XVIII/2020, Law No. 13 of 2022 strengthened the mandate for public participation to make it more meaningful (meaningful participation) in the formation of laws and regulations, both offline/online and online. This mandate applies to all legislators at the national and local levels. Provinces, autonomous cities, or parts of districts characterized by cities are all examples of urban areas. The purpose of this article is to elaborate on the concept of implementing meaningful public participation in the formation of urban regulations through the lens of smart urban governance. This review employs systematic literature review tools in conjunction with qualitative descriptive analysis to create an in-depth framework of the concept of meaningful public participation in the urban context and the development of smart legislation in urban governance. The legislative process in urban areas, both offline and online, can be integrated in one digital ecosystem through the Smart-Legislation platform, facilitating and facilitating community or city residents to participate and engage in the entire process of forming legislation at the city level